A Case Report of Inflammatory Disseminated Superficial Porokeratosis: An Eruptive Pruritic Papular Variant of Porokeratosis - Ling-Ling Luo; Hao Chen; Xue-Si Zeng; Pan-Gen Cui (Wolters Kluwer Health, 2021)
Abstract. Introduction:. Eruptive pruritic papular porokeratosis (EPPP) is a rare variant of porokeratosis. Several cases of this varient of porokeratosis had been reported. Here, we reported an old man with this rare kind of porokeratosis which is often eruptive and pruritic. Case report:. A 72 years-old Chinese man presented to our hospital with intensively pruritic papular lesions on his trunk and limbs. Physical examination showed numerous scattered keratotic papules measuring 35 mm in diameter on his trunk and extremities. Some coalesced into anannular lesion with a slightly raised peripheral red rim. A tissue biopsy revealed the presence of a cornoid lamella. The patient was diagnosed with EPPP. After 3-months' treatment of antihistamines and topical steroid agents, the lesions and the pruritus were diminished. Discussion:. EPPP predominantly happens in an old male demographic. Patients with EPPP often develop pruritic papules spread on the body with or without preexisting typical porokeratosis lesions, and the lesions can subside within few months, leaving small brown spots or annular lesions. EPPP has the unique histological characteristic of porokeratosis cornoid lamella. The mechanism of EPPP is still unknown. It is important for clinicians to be aware of a disseminated pruritic papules as a manifestation of EPPP. Conclusion:. The lesion of porokeratosis can be manifested as eruptive papules with intensive itch. When a patient develops eruptive pruritic papules, it is necessary to consider the possibility of EPPP. Histopathology is necessary for diagnosis.